ANALISIS TOTAL PRODUCTIVE MAINTENANCE (TPM) MENGGUNAKAN OVERALL EQUIPMENT EFFECTIVENESS (OEE) DAN SIX BIG LOSSES PADA MESIN THERMOFORMING DI PT. KEMASAN CIPTATAMA SEMPURNA - Nur Diansyah Rizky Pratama (Jurusan Teknik Mesin, 2022)
PT. Kemasan Ciptatama Sempurna is a company engaged in the packaging sector with its main products, namely Styrofoam and Launch Box. In the Launch Box production section , the machine works 24 hours every day due to high market needs, one of which is the thermoforming machine. This is what makes the thermoforming machine stay in optimal condition, therefore it is necessary to apply the maintenance method. TPM is an alternative approach to equipment maintenance that strives to achieve zero damage and zero defects. Besides that TPM is also a an approach to keep current plants and equipment to a higher level of productivity through cooperation between all organizational areas within the company. This study aims to calculate the value of Overall Equipment Effectiveness and Six big losses at thermoforming machine so that it can reduce losses that cause the machine to not be in optimal condition by providing suggestions based on the TPM pillar. The results showed that the value of Overall Equipment Effectiveness of the thermoforming machine from January to September was 39.41% with an average value of availability of 94.78%, performance rate 73.51%, and quality rate 56.44%. From the value of Overall Equipment Effectiveness (OEE), then we look for losses that make the value of the Overall Equipment Effectiveness (OEE) component low by using six big losses and analysis using Pareto and fishbone diagrams. From the Pareto diagram analysis, it was found that the highest losses caused the value of the Overall Equipment Effectiveness (OEE) component to be low, namely reduced yield and scrap losses and reduced speed losses with the respective percentage losses of 39.79% and 36.53%. There are several recommendations that can be made based on the 8 pillars of TPM, including autonomous maintenance; planned maintenance; quality integration; focused improvement; early equipment management; training and education; safety, healty, environtment; and TPM in administration.